PENGETAHUAN TENTANG TUHAN DALAM TEKS SERAT SASTRA GENDHING - Yuli Kurniati Werdiningsih; Setia Naka Andrian (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
This study aims to describe the knowledge of God in the text of Serat Sastra Gendhing.This research is a qualitative type. The source of the research data is Serat Sastra Gendhing text editing. The research data are words, phrases, clauses, and sentences that contain knowledge about God in the text of Serat Sastra Gendhing. Data is collected through a classification process; identification; inventory. Data were analyzed by hermeneutic studies through methods of reduction, interpretation, and conclusions. The results of research in the form of knowledge about God contained in the text of Serat Sastra Gendhing as follows. God is in rasa, God is known in the union between rasa and pangrasa, knowledge of God involves all aspects of human beings. Knowledge about God is not only reflected in worship, but also in the rasa, pikiran, and perbuatan that implement the attributes of God.